Visual Comfort Analysis of Office Buildings in The Gedhong Hinggil, Rectorate Building of Widya Mataram University - Ayuningtyas, Nurina Vidya; Adianti, Istiana; Kindi, Kindi (Universitas Muhammadiyah Surakarta, 2025)
Light will fall on an object and be reflected back to our eyes so we can see these objects. Visual comfort will be achieved when there is sufficient lighting in a room. If the light that comes in is less or more, it will disturb the comfort of human vision. The objective of this study is to delineate the area in the Gedhong Hinggil Dalem Mangkubumen Building to see whether it meets comfort standards for office buildings. The purpose of this study is to analyze whether the Gedhong Hinggil building is suitable to be used as a workplace, so that it can provide input to campus managers to be able to improve the condition of the workplace without eliminating the authentic hierarchy of the traditional Gedhong Hinggil building. On average, the intensity values ​​for rooms in the rectorate do not meet SNI requirements. The west side and east side areas already have quite wide openings. This building is a cultural heritage building that cannot be changed, to comply with the established SNI standards for work spaces or offices, the light intensity in the room can be increased by adding artificial lighting (lamps). The final result of this study shows that the Gedhong Hinggil Dalem Mangkubumen building does not meet the standards if used as an office building. This is because the building originally functioned as the residence of the Crown Prince.